Implementasi Siaran TV Sekolah Sebagai Media Informasi Kegiatan Sekolah TK Inplayschool - Yulia Anastasia Anggori; Sri Watini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This study discusses the implementation of school television broadcasts which are used as a medium for information on school activities for Kindergarten Inplayschool which is a kindergarten school that has interesting activities. So far, various information has been conveyed through cellular communication media, brochures, pamphlets and teaching materials with all their limitations. Along with the development of the era where everything has changed based on digital, it is necessary to have information media facilities that are able to answer all the challenges of the digital era. This research is based on the importance of audio-visual-based information media that is able to convey information in a package that is much more attractive, flexible, effective and has a wide reach. The research uses a conceptual method which is a qualitative research with data collection techniques, namely observation, question and answer, and documentation without having prepared instruments like research with a quantitative approach. This school TV was developed by Mrs. Sri Watini, et al, which is a TV streaming service resulting from the industrial revolution 4.0 which is the best solution for institutions in conveying a variety of activities. The results of this study are that Inplayschool Kindergarten has implemented school TV broadcasts as an effective medium of information such as learning information. as well as educational entertainment.